2022
DOI: 10.1007/s40121-022-00682-0
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime/Avibactam-Based Versus Polymyxin B-Based Therapeutic Regimens for the Treatment of Carbapenem-Resistant Klebsiella pneumoniae Infection in Critically Ill Patients: A Retrospective Cohort Study

Abstract: Introduction: Considering the importance of ceftazidime/avibactam (CAZ/AVI) and polymyxin B (PMB) in treating carbapenem-resistant Klebsiella pneumoniae (CRKP) infection, it is essential to evaluate the efficacy and safety of these agents and provide appropriate medical advice to clinical specialists. Methods: We conducted a retrospective cohort study in two Chinese tertiary hospitals for critically ill patients with CRKP infection who received at least 24-h CAZ/AVI-based or PMBbased treatment. A binary logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The study did not reveal any significant difference in mortality or clinical cure among patients with or without combination therapy with other antibiotics, which included minocycline, polymyxins, metronidazole, levofloxacin, and fosfomycin. This is in concordance with other studies where there was no reduction in mortality with combination therapy whereas, a study on critically ill patients with CRE infections showed a lower 30-day mortality rate [4,27,28].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The study did not reveal any significant difference in mortality or clinical cure among patients with or without combination therapy with other antibiotics, which included minocycline, polymyxins, metronidazole, levofloxacin, and fosfomycin. This is in concordance with other studies where there was no reduction in mortality with combination therapy whereas, a study on critically ill patients with CRE infections showed a lower 30-day mortality rate [4,27,28].…”
Section: Discussionsupporting
confidence: 92%
“…Septic shock is associated with high mortality and the pharmacokinetics of most drugs cannot be relied upon in this situation. Other studies depicted good efficacy with varying percentages of patients with sepsis or septic shock and a study by Vena et al demonstrated good clinical efficacy even when the majority of the study patients had septic shock [4,21,22].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, analysis of post hoc predicted exposures for adults from the phase III program showed that in multiple subgroups of patients with markers of severe/critical illness, including APACHE II score > 10, systemic inflammatory response syndrome, bacteremia, fever, and augmented renal CL, approved adult doses achieved joint target attainment > 90% 5 . In addition, several real‐world studies have reported positive outcomes for the recommended ceftazidime‐avibactam doses in critically ill adult patients 33–35 . Our modeling approach and the resulting dose recommendations based on matching exposures for pediatric patients (including renal impairment) with adults suggests that the recommended pediatric doses will also be suitable for critically ill children.…”
Section: Discussionmentioning
confidence: 99%